SOLUTIONS OF NONLINEAR BOUNDARY SYSTEM WITH COUPLED INTEGRAL BOUNDARY CONDITIONS - BUTRIS, RAAD NOORI; FARIS, HEWA SALMAN (E-Jurnal Matematika; Vol 12 No 4 (2023), 2023)
This article presented some theorems on a novel non-linear multiple Integro-differential equations of boundary T-system. It has been studied the numerical-analytic method and Banach fixed point theorem for the existence and approximation of the solutions over considered boundary system in compact space. In this work, we demonstrate that the mention methods can be discussed and analyzed for the existence and uniqueness, of a solution for the vector system. The paper satisfies the Hölder condition.